THE PENTAHELIX MODEL: STRENGTHENING INNOVATION POTENTIAL AND FOSTERING SCIENCE AND EDUCATION INTEGRATION - Nugraha, Yorri Kusuma; Sumaryatiningsih, Siti (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The Pentahelix model is a holistic and collaborative approach aimed at increasing the potential for innovation  and optimizing the integration of science and education. This model consists of five main elements: A(Academy) - B(Business) - C(Community) - G(Government) - M(Media). This study addresses the issue of program failures in both government and private sectors due to the suboptimal role of these five factors. The purpose of the study is to investigate the impact of implementing the model on increasing the potential for innovation  and promoting the integration of science and education. Additionally,  the  effectiveness of the model in supporting cross-functional collaboration is evaluated, the role of each stakeholder is analyzed, and  factors influencing successful implementation are identified. Research methods include a detailed literature review, case studies on the implementation of the Pentahelix model in different global contexts, and qualitative data analysis. Research results show that close collaboration among the five elements is an ideal model for building an innovation ecosystem and effectively integrating science, education, and practical needs. The  implementation of this model shows that government, industry and academia are having a positive impact on creativity, research and development. However, challenges such as political differences and conflicts of interest remain obstacles. The synergies and interactions between Pentahelix stakeholders contribute to building an innovation ecosystem that supports creativity, research and development. By exploring successful examples and best practices, this study highlights the flexibility and effectiveness of models that foster cross-functional collaboration. The study's conclusions highlight the importance of involving stakeholders and overcoming new barriers. The Pentahelix model therefore, serves as an effective foundation for the development of an inclusive and sustainable innovation ecosystem. This study contributes to a practical understanding of the implementation of this model to promote innovation and science integration in a changing global context.